2011
DOI: 10.1097/tp.0b013e31820f42d9
|View full text |Cite
|
Sign up to set email alerts
|

Age, Exclusion Criteria, and Generalizability of Randomized Trials Enrolling Kidney Transplant Recipients

Abstract: Background The proportion of elderly (≥65 years) kidney transplant recipients (KTRs) doubled in the United States (US) from 1999 – 2008. Given higher mortality, more medication side effects, and less rejection among elderly KTRs, optimal care of these patients may require tailored decisions about transplant therapeutics. It is unknown whether participants in transplant clinical trials – which generate the best evidence for patient care – are representative of the aging population of KTRs. Methods Using PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Indeed, a meta-analysis of more than 500 studies revealed that trial participants who underwent kidney transplantation were significantly younger than the overall kidney transplant recipients in the US. (5) Moreover, recognizing the necessity to respond to the rapid demographic shift, the Food and Drug Administration (FDA) has recently encouraged clinical trials in the elderly (6) to explore age-specific aspects of immunosuppressants.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a meta-analysis of more than 500 studies revealed that trial participants who underwent kidney transplantation were significantly younger than the overall kidney transplant recipients in the US. (5) Moreover, recognizing the necessity to respond to the rapid demographic shift, the Food and Drug Administration (FDA) has recently encouraged clinical trials in the elderly (6) to explore age-specific aspects of immunosuppressants.…”
Section: Introductionmentioning
confidence: 99%
“…43 A recent meta-analysis revealed that kidney transplant recipients participating in clinical trials in the US were significantly younger. 44 Older age as an exclusion criterion was evident in 30% of studies. Obviously, clinical trials in transplant medicine do not consider the clinical reality of a steadily increasing volume of older transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, older recipients have been underrepresented in pivotal immunosuppression trials but clinically are usually treated with those same regimens. (4) Therefore we studied CNI disposition in a large population of kidney transplant recipients in three adult age groups; young (18–34 years), middle (35–64 years) and older (65–84 years) to define age related drug disposition changes adjusting for important demographic, clinical, and genetic factors.…”
Section: Introductionmentioning
confidence: 99%